Fractional CO2 Laser vs. Platelet Rich Plasma (PRP) in the Management of Striae Distensae: A Comparative Study - بدور رولا; الأشقر فاتن (Latakia University Journal -Medical Sciences Series, 2020)
BACKGROUND: Striae distensae (SD) are linear scars that result from physiological or pathological stretching of the skin. They are very common and cause cosmetic and psychological concerns for many. OBJECTIVE: to evaluate and compare the efficacy of Fractional CO2 laser and Platelet Rich Plasma (PRP) in the management of SD. MATERIALS AND METHODS: 30 patients underwent 4 treatment sessions of monthly intervals. The area was divided in half. One half was treated with fractional CO2 laser (Smartxide2) which was set to the parameters of severe atrophic scars. The other half was treated with PRP after centrifuging the patient’s own blood for 10 minutes at a speed of 3000 RPM. Patients were photographed before each session and one month after the last session. Clinical improvement was evaluated through comparing the photographs by a blinded dermatologist. In addition, the patient’s satisfaction was assessed too. RESULTS: All patients showed improvement with both methods, but there was more improvement with PRP which was statistically significant. Regarding both methods, we found no relationship between response to treatment and gender, color of the striae, or their location. CONCLUSION: Both methods give an average improvement in the management of SD. PRP showed to be more effective with less side effects and shorter downtime and got more patients’ satisfaction.